2019
DOI: 10.1097/dbp.0000000000000737
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Anxiety, Parenting Stress, and Preschoolers' Behavior Problems: The Role of Child Self-Regulation

Abstract: Objective: Maternal anxiety is a well-known risk factor for early childhood behavior problems. In this study, we explore (1) whether parenting stress mediates this relation and also (2) whether child factors, namely self-regulation, modify the influence of maternal well-being on child externalizing and internalizing problems at 4 years of age. Method: Mothers taking part in the Growing Up in Singapore Towards Healthy Outcomes cohort completed the Spielb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 30 publications
4
15
0
1
Order By: Relevance
“…Greater prenatal anxiety was associated with greater postpartum parenting stress, as anticipated, although it did not necessarily portend lower parenting satisfaction. Anxious individuals tend to experience a greater threat than is necessary for the situation, perceiving various aspects of parenting or caring for their child as threatening or potentially more dangerous than is warranted (Tsotsi et al, 2019). Thus, it makes sense that more anxious expectant fathers might experience parenting as particularly stressful relative to less anxious fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Greater prenatal anxiety was associated with greater postpartum parenting stress, as anticipated, although it did not necessarily portend lower parenting satisfaction. Anxious individuals tend to experience a greater threat than is necessary for the situation, perceiving various aspects of parenting or caring for their child as threatening or potentially more dangerous than is warranted (Tsotsi et al, 2019). Thus, it makes sense that more anxious expectant fathers might experience parenting as particularly stressful relative to less anxious fathers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the amount of social support, the economic status of the mothers might also be related to maternal parenting stress. The SES was by most studies measured via education and/or income separately [11,13,35,36,39,[54][55][56]. Together, these studies suggested evidence for an association between having a higher maternal educational level and lower parenting stress; and inconsistent evidence for an association between income and maternal parenting stress.…”
Section: Situational Factors and Parenting Stressmentioning
confidence: 99%
“…The procedures used in this task have been previously reported 60 . Briefly, we used SE and NSE counterbalanced versions of an inhibitory control task.…”
Section: Inhibitory Controlmentioning
confidence: 99%